Analysis of The Effect of Infrastructure Investment on Economic Growth in Indonesia: Linear Regression Model Approach - Rijal, Syamsu; S, Masnawati; Iwang, Baso (International Journal of Business, Law, and Education, 2023)
This study investigates the relationship between infrastructure investment and economic growth in Indonesia, given the economic challenges posed by the COVID-19 pandemic. With the country's focus on a 20-year development plan, emphasizing human capital and global competitiveness, the research aims to provide insights for policymakers to formulate effective economic strategies. Using a quantitative approach and linear regression analysis, the study examines data spanning 2017-2022 sourced from official government platforms. Infrastructure investment, economic growth, and control variables such as inflation, government spending, and population growth are analyzed. The findings underscore the importance of stable inflation, efficient government spending, and controlled population growth for sustained economic development. In conclusion, this research provides valuable insights for policymakers, suggesting a need to prioritize infrastructure projects to stimulate economic growth. However, the study encourages further research to identify specific infrastructure initiatives that yield the most significant impact on economic development.